Analisis Peta Administrasi dalam Mengidentifikasi Ketidakjelasan Batas Nagari dan Informasi Wilayah Nagari Sungai Jambu Di Kecamatan Pariangan - Nesa Riska Pangesti; Gelvin Abi Asrifhat; Alya Putri; Fahmi Muhammad Idris; Najwa Tri Aulia; Alviqri Febrino (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Administrative maps are essential instruments for providing spatial information regarding regional boundaries and territorial conditions. However, in several nagari areas, there are still issues related to unclear administrative boundaries and limited regional information presented on existing maps. These limitations can lead to difficulties in regional management, development planning, and the dissemination of information to the community. This “Kuliah Kerja Nyata (KKN)” activity aims to analyze administrative maps to identify boundary ambiguities and to enhance incomplete regional information, including land use characteristics. The methods employed in this study include secondary data collection from existing administrative maps, field observations, and spatial data processing using Geographic Information Systems (GIS). In addition, land cover analysis was conducted using satellite imagery to identify land use patterns within the study area. The results indicate that several administrative boundaries in the previous maps were not clearly delineated, and information on public facilities and other territorial elements was limited. Furthermore, land cover analysis reveals that the study area is predominantly covered by primary and secondary forests, with other land uses consisting of paddy fields, settlements, and open land. The spatial distribution of land use reflects a strong relationship between the physical characteristics of the area and community activities, particularly in the agricultural sector. Through the remapping and analysis process, a more accurate and informative administrative map was produced, featuring clearer boundaries and additional spatial information such as public facilities, road networks, and land cover. This map is expected to serve as a reliable source of spatial information to support regional planning and sustainable land management for both the nagari government and the local community.